Presenting Morphing Shape Illusion Enhanced Sense of Morphing Virtual Object With Weight Shifting VR Controller by Computational Perception Model - Shigeyama, Jotaro (IEEE computer graphics and applications, 2023)
The haptic sensation is crucial for virtual reality, as it gives the presence of objects in a virtual world and thus gives a greater sense of immersion. To provide a sense of the shape of handheld objects, a haptic device that changes weight distribution is proposed. It is known that the visual feedback enhances the haptic sensation of shape, and it is also known that it does for morphing shape as well. Our previous publication presented a perception model for the static shape of a virtual object. In this article, we extend the model to produce a plausible sense of the morphing shape of handheld objects. Our stochastic model predicts the proper weight actuation for the weight-shifting haptic device, which users can plausibly feel while reducing hardware effort. We evaluated our perception model and resulted in the model accuracy average of 8.1% error. Using this perception model, the amount of weight actuation at 75% probability of plausibility is reduced up to 37%